Ca(2+)-Independent Protein Kinase C Apl II Mediates the Serotonin-Induced Facilitation at Depressed AplysiaSensorimotor Synapses - Manseau, Frédéric (J Neurosci, 2001)
At nondepressed Aplysia sensory to motor synapses, serotonin (5-HT) facilitates transmitter release primarily through a protein kinase A pathway. In contrast, at depressedAplysia sensory to motor synapses, 5-HT facilitates transmitter release primarily through a protein kinase C (PKC)-dependent pathway. It is known that only two phorbol ester-activated PKC isoforms, the Ca(2+)-dependent PKC Apl I and the Ca(2+)-independent PKC Apl II, exist in the Aplysia nervous system. For the first time, we have now been able to functionally determine which isoform of PKC is involved in a particular form of plasticity. We microinjected cultured sensorimotor pairs of neurons with various PKC constructs tagged with the enhanced green fluorescent protein as a reporter for successful plasmid expression. Our results demonstrate that short-term facilitation of depressed synapses is mediated by PKC Apl II. Dominant-negative PKC Apl II, but not dominant-negative PKC Apl I, disrupted the normal kinetics of 5-HT-induced facilitation by completely blocking its rapid onset. This effect was specific to depressed synapses, because dominant-negative PKC Apl II did not inhibit 5-HT-mediated facilitation of nondepressed synapses. Our results suggest that not only different signal transduction pathways but also different isoforms of a specific cascade may mediate physiological responses according to the state of a synapse.